(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
A partial skull of an odontocete cetacean from Middle Pliocene sediments of Monte Voltraio (Pisa Province, Tuscany, Italy) is examined. This fossil, erroneously referred to the family Ziphiidae and described in the past as holotype of the species Hyperoodon pusillus, is assigned here to the genus Kogia (family Kogiidae). The species Kogia pusilla is redescribed and compared to the living species K. breviceps and K. simus. Phylogenetically, an old separation (at least in the Lower Miocene) of Kogiidae and Physeteridae is suggested. The lack of substantiated kogiid records until the Upper Miocene is probably due to the rarity of these cetaceans. Phyletic analysis within the Kogiidae is undertaken and supposed apomorphies in the morphology and/or the extension of the supracranial basin that houses the large air sacs and the spermaceti organ are considered.